First Description of Adult Males of Four Species of the Treehopper genus Tricentrus Stål from China (Hemiptera, Membracidae, Centrotinae, Tricentrini) - Li, Feng-E; Yang, Lin; Long, Jian-Kun; Chang, Zhi-Min; Chen, Xiang-Sheng (Zootaxa, 2020)
Adult males are described and illustrated for the first time for four Chinese species of the treehopper genus Tricentrus previously known only from females: T. albipennis Kato, 1930, T. floripinnae Yuan & Cui, 1987, T. foliocornatus, Yuan & Fan, 2002 and T. oedothorectoidis Yuan & Fan, 2002.